2013
DOI: 10.12688/f1000research.2-177.v1
|View full text |Cite
|
Sign up to set email alerts
|

Fecal transplantation does not transfer either susceptibility or resistance to food borne listeriosis in C57BL/6 and BALB/c/By mice

Abstract: The composition of the intestinal microbiota has wide reaching effects on the health of an individual, including the development of protective innate immune responses.  In this report, a fecal transplantation approach was used to determine whether resistance to food borne listeriosis was dependent on the murine gut microbiota.  Transplantation of BALB/c/By feces did not increase the susceptibility of C57BL/6 mice to Listeria monocytogenes infection.   Likewise, transplantation of C57BL/6 fecal matter did not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The endogenous microbiota of 12-week-old homozygous fat-1 transgenic and WT mice were depleted by treatment with a single dose of streptomycin (Sigma-Aldrich, St. Louis, MO). This process has previously been validated for fecal microbiota transplantation in conventional mice (25). It can transiently reduce by 90% the density of cecal bacteria recovered using anaerobic culture conditions and is known to return to normal levels within 3-4 days (26).…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The endogenous microbiota of 12-week-old homozygous fat-1 transgenic and WT mice were depleted by treatment with a single dose of streptomycin (Sigma-Aldrich, St. Louis, MO). This process has previously been validated for fecal microbiota transplantation in conventional mice (25). It can transiently reduce by 90% the density of cecal bacteria recovered using anaerobic culture conditions and is known to return to normal levels within 3-4 days (26).…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…Before each fecal transfer treatment, 1 g fecal pellets were collected from eight naïve donor mice, pooled, and placed in 5 mL Dulbecco's PBS (Life Technologies, Grand Island, NY). The fecal transplantation was performed as described previously (25).…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…To that end, we performed fecal transfer experiments as shown in Fig. A, using modified versions of milder forms of antibiotic treatments as to not completely deplete the normal mouse microbiome, which has been shown to be essential to the development of murine EAE . The data demonstrated that naïve C57BL/6mice (CD44WT) immunized with MOG and treated with streptomycin and ampicillin, followed by fecal transfer from naïve CD44KO mice showed a significant decrease in EAE clinical scores when compared to similar mice given feces from naïve CD44WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During feces transfer experiments, fresh stool pellets from DCA‐treated and ‐untreated mice followed by 2‐weeks' washout of DCA were suspended in reduced PBS (0.1 g/1 mL), homogenized, centrifuged at 800 g for 5 min and the supernatant was collected. Three hundred μL of supernatant was transplanted to 4‐week‐old Apc min/+ mice, which were given a gavage of streptomycin (20 mg) daily for 3 days before FMT to deplete the native gut microbiota as previously described . During transfer experiments, the mice were inoculated for a total of 16 times over the subsequent 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Three hundred lL of supernatant was transplanted to 4-week-old Apc min/1 mice, which were given a gavage of streptomycin (20 mg) daily for 3 days before FMT to deplete the native gut microbiota as previously described. 23,24 During transfer experiments, the mice were inoculated for a total of 16 times over the subsequent 8 weeks.…”
Section: Fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%